2020
DOI: 10.24251/hicss.2020.219
|View full text |Cite
|
Sign up to set email alerts
|

New Kid On The Block! Understanding Blockchain Adoption in the Public Sector

Abstract: Blockchain has been heralded as a technology that can transform entire sectors, including the public sector where blockchain applications are believed to bring a wide range of benefits. The public sector is lagging behind, however, in its actual adoption of blockchain technology, and our understanding of the factors that explain the slow adoption rate, is lacking. Based on seven case studies of blockchain projects at various adoption stages, this research contributes to our understanding of what factors influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Loklindt, et al [38], Mohammed, Potdar and Yang [7], Post, et al [39], Hoxha and Sadiku [40], and Holotiuk and Moormann [20] investigated BCT adoption for the different industries including shipping and land record management. They showed that easy verification of transactions, data accuracy and reliability, and cost reduction influence an organization's decision to adopt BCT; Kulkarni and Patil [41] and Koster and Borgman [42] mentioned that the firm scope, learning culture, top management, customer readiness, competitive pressure, and government policies influence BCT adoption in banking and the public sector. Moreover, Albrecht, Reichert, Schmid, Strüker, Neumann and Fridgen [27] studied the post-decision stage of the BCT adoption.…”
Section: Adoption Of Blockchain Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Loklindt, et al [38], Mohammed, Potdar and Yang [7], Post, et al [39], Hoxha and Sadiku [40], and Holotiuk and Moormann [20] investigated BCT adoption for the different industries including shipping and land record management. They showed that easy verification of transactions, data accuracy and reliability, and cost reduction influence an organization's decision to adopt BCT; Kulkarni and Patil [41] and Koster and Borgman [42] mentioned that the firm scope, learning culture, top management, customer readiness, competitive pressure, and government policies influence BCT adoption in banking and the public sector. Moreover, Albrecht, Reichert, Schmid, Strüker, Neumann and Fridgen [27] studied the post-decision stage of the BCT adoption.…”
Section: Adoption Of Blockchain Technologymentioning
confidence: 99%
“…Top management support is an integral part of an organization's decision to adopt new technology. The lack of leadership support reduces the chances of adopting an innovation such as BCT [42]. De Castro, Tanner and Johnston [26] found that an organization adopts BCT when its leadership provides required resources.…”
Section: Top Management Support (Tms)mentioning
confidence: 99%
“…Based on blockchain cases, Koster and Borgman (2020) have shown that the success of projects in BT adoption is significantly influenced by BT hype, top management support, regulatory environment and trust among blockchain partners (Koster and Borgman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ainsworth and Alwohaibi (2017) proposed a model for tax administration in GCC for VAT, concentrating trust as an essential element of effective tax governance leaving the scope for further studies of BT adoption in the areas of other tax administrations. Koster and Borgman (2020) suggested future research to be conducted by quantifying the results for the factors influencing BT adoption. They also recommended further studies to be conducted to understand the perceived trust factor in a more considerable extent.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation